1999
DOI: 10.1097/00004703-199910000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Physician Prescriptions and Adherence to Treatment Among Children with Cystic Fibrosis and Their Mothers

Abstract: This investigation examined factors related to adherence to treatment regimens for children with cystic fibrosis (CF) and their mothers. Subjects were 45 children with CF who ranged in age from 6 to 10 years and their mothers. Findings revealed that children's and parents' reports of level of adherence were related to their knowledge of the specific details associated with medically prescribed treatments. In this sample, 12% to 32% of mothers did not have an accurate understanding of physician recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 0 publications
0
35
0
1
Order By: Relevance
“…These authors reported a significant association between social class and mothers' and fathers' knowledge of CF, but did not investigate the association between class and health outcomes. Studies of medical therapy adherence in children with CF and their families have shown that caregiver knowledge of specific treatment regimens has variable effects on adherence [28][29][30][31][32]. None, however, have examined the effect of caregiver's overall level of education on health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported a significant association between social class and mothers' and fathers' knowledge of CF, but did not investigate the association between class and health outcomes. Studies of medical therapy adherence in children with CF and their families have shown that caregiver knowledge of specific treatment regimens has variable effects on adherence [28][29][30][31][32]. None, however, have examined the effect of caregiver's overall level of education on health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that part of a successful transition relies upon ensuring that sufficient information about treatment plans and the disease itself has been understood [8]. The goal -a higher level of knowledge -has been correlated with better disease management and, to some extent, treatment compliance [9][10][11][12][13]. Because much of CF care relies on self-management, these findings underscore the importance of a solid knowledge base.…”
Section: Introductionmentioning
confidence: 99%
“…When a patient or a parent/caregiver gets the knowledge about management and how these management lead to better health, they are likely to pursue care and comply with the recommended treatment procedure (Levers et al, 1999 Information on one's illness may be a motivating factor to adhere to the treatment regime. When people take a step to learn about their condition, they will make an effort to control it (Weiss et al, 2003).…”
Section: Parent/caregiver's Knowledgementioning
confidence: 99%